Superficial lymphangioma/Circumscribed angiokeratoma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
Superficial lymphangioma and circumscribed angiokeratoma are superficial, usually localized vascular malformations. Although affecting lymphatic vessels, lymphangioma characteristically undergoes intralesional hemorrhages. The latter can make the differential diagnosis from circumscribed angiokeratoma difficult.